Comparison of injuries in classic and skating Nordic ski techniques - Butcher, J. D.; Brannen, S. J. (Clinical Journal of Sport Medicine, 1998)
OBJECTIVE: To compare types and anatomic distribution of injuries between cross-country skiers using the classic and skating ski techniques. DESIGN: Descriptive self-administered survey. SUBJECTS: Midlevel competitors in the 1996 American Birkebeiner cross-country ski marathon (55 km). DESCRIPTION OF SURVEY: A self-administered 21-item questionnaire regarding skiing-related injuries occurring during training before the race or during the marathon. The respondent was asked for information regarding any skiing-related injury or complaint that occurred during training or while participating in the American Birkebeiner ski race. This tool also collected information regarding training habits, equipment selection, and skier demographics. Responses were coded on a Mark-Sense form and compiled by a computerized code reader. MAIN RESULTS: A total of 833 surveys were returned for an overall response rate of 55%. The overall self-reported injury rate for the surveyed group was 234 per 1000 skiers (i.e., 23.4% of skiers sustained an injury during the race). Most of these injuries were minor; only 4.6% of all skiers reported lost training time because of a race injury, and only 2.8% of all skiers sought treatment from a health care provider for a race-related injury. There was no statistically significant difference between the two techniques either in overall injury rate (p=0.33) or in the location of the injury (p=0.158). The injury rates were 23% and 27%, respectively, for skating and classical techniques. The incidence of more serious injuries (those requiring medical attention) was 2.7% for skaters and 3.1% for classical skiers. No statistically significant relation was found between pole length and the development of injuries. In addition, the likelihood of sustaining an injury was independent of age and training distance. CONCLUSIONS: The overall injury rates in this study were much higher than those previously reported in the literature, but no significant difference in injuries between the two skiing techniques was found. The incidence of more severe injuries, defined as those requiring medical treatment, was consistent with previous reports. Prior assumptions regarding equipment relationships to injuries were not substantiated by the findings. In spite of significant changes in the equipment and technique designed to enhance speed, cross-country skiing remains a safe sport, with its participants relatively free of serious injuries. Further investigation is required to determine whether other aspects of the sport, such as pole grip design, ski construction, and skier skill level, have any relation to injury patterns.